Effectiveness of Management Accounting Systems, Management Control Systems, and Environmental Uncertainty on Managerial Performance with Decentralization as A Moderation Variable - Difla (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2024)
This research aims to determine "the effectiveness of management accounting systems, management control systems and environmental uncertainty on managerial performance with decentralization as a moderating variable". The method in this research is quantitative with primary data sources. The population in this study was the Regional General Hospital (RSUD) in DKI Jakarta. The samples for this research were heads of divisions, heads of subfields, heads of sections, heads of subsections as well as heads of installations and staff at Regional General Hospitals in DKI Jakarta with a total of 104 respondents. The data analysis used in the research was SEM PLS version 3.00 data analysis. Based on the results of research using hypothesis testing, it shows that the Management Accounting System has a significant effect on Managerial Performance. The Management Control System does not have a significant effect on Managerial Performance. Environmental Uncertainty has a significant influence on Managerial Performance. Decentralization does not moderate the influence of the Management Accounting System on Managerial Performance. Decentralization moderates the influence of Environmental Uncertainty on Managerial Performance. Decentralization moderates the influence of the Management Control System on Managerial Performance